Blue Ocean Strategy: Case Study on PT. Wismilak Inti Makmur, Tbk - Liman, Chandya (ProBisnis : Jurnal Manajemen, 2023)
PT. Wismilak Inti Makmur is an Indonesian cigarette company that has started commercial activities producing hand-held cigarettes since 1962 in Surabaya. This research was conducted to formulate and test the blue ocean strategy in the cigarette industry. The research method used is based on literature studies to understand consumer preferences and current industry trends. By implementing the blue ocean strategy, it is hoped that WIIM can get out of the red ocean and have a new market in the blue ocean. This research provides input in developing innovations that can be carried out by the cigarette industry in the face of intense competition using research methods The Four Actions Framework and Six Paths Framework.